Pengembangan Video Animasi Berbantuan Doratoon Pada Tema Makanan Sehat di Kelas V Sekolah Dasar - Ayu Dia Melisa; Muhammad Noer Fadlan (Lembaga Pendidikan Islam Ma'aarif NU Kabupaten Magetan, 2023)
This article presents a study on the development of video animation assisted by Doratoon to enhance students' understanding of healthy food in fifth-grade elementary school. The research method used is research and development, and data collection is done through interviews, questionnaires, tests, and documentation. The findings show that students and teachers have a need for more varied and engaging learning media, and the development of video animation is seen as a solution to address this need. The article emphasizes the importance of using technology in education and the role of media in enhancing the learning experience. The study concludes that the video animation assisted by Doratoon on the theme of healthy food is of good quality and suitable for use. The evaluation results from individual and small group testing show that the video is practical and effective in improving students' understanding. The validation from media experts and thematic learning experts also confirms the validity of the video. Therefore, the video animation assisted by Doratoon can be used as an effective learning media to teach healthy food to students.